(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the improvement in nurses’ practice confidence in mental health care for women with cancer following participation in a capacity-building training program. Methods: A quasi-experimental study with a pre- and post-intervention comparison was conducted involving 170 nurses. Results: The level of confidence in providing mental health care demonstrated a statistically significant improvement. Specifically, confidence in managing anxiety exhibited the most substantial increase, rising from 2.59 ± 0.93 to 2.84 ± 0.94. Nurses’ awareness of specialist mental health services increased after training. Conclusion: The capacity-building training program significantly enhanced nurses’ mental health care practices. Strengthening training programs and promoting the use of mental health screening tools are essential to improving the quality of comprehensive health care for women with cancer.